Mobile synbiotope microbiocenosis against pathogens - M. V. Lakhtin; V. M. Lakhtin; S. S. Afanasyev; A. L. Bayrakova; A. V. Karaulov; M. S. Afanasyev; V. A. Alyoshkin (Acta Biomedica Scientifica, 2016)
Based on own results, conception of mobile synbiotope microcenosis against pathogens as well as new antimicrobial strategies connected to conception are proposed. Synbiotope mobility is determined by the presence (in varying combinations] of cofunctioning antimicrobial ways which can be realized with participation of highly molecular mass metabolites of probiotic bacterial cultures. Thus, probiotic enzymatic systems (proteinases, EPS-depolymerases and/ or oxidoreductases] reveal cofunctioning with probiotic lectins. New antipathogen strategies use technological advantages of choice and selection of symbiotic strains and consortia producing synergistical enzyme-lectin-glycoconjugate systems against microfungal and Gram-positive pathogens. Additional strategies involve construction of synbiotic systems supporting probiotic compartment of biotope.